The Lipoprotein Transport System in the Pathogenesis of Multiple Myeloma: Advances and Challenges - Lazaris, Vasileios; Hatziri, Aikaterini; Symeonidis, Argiris; Kypreos, Kyriakos E. (Frontiers in Oncology, 2021)
Multiple Myeloma (MM) is an incurable neoplastic hematologic disorder, characterized by malignant plasma cell infiltration, mainly in the bone marrow. Multiple factors such as lipid metabolism, obesity, and age have been associated with disease development. Although, the precise pathogenetic mechanisms remain unknown, abnormal lipid and lipoprotein levels have been reported in MM patients. Interestingly, patients with higher APOA1 levels, the major apolipoprotein of High Density Lipoprotein (HDL) appear to have better overall survival. The limited existing studies regarding serum lipoproteins in MM are inconclusive and often contradictory. Nevertheless, it appears that deregulation of the lipoprotein transport system may facilitate the development of the disease. Here, we provide a critical review of the literature on the role of lipids and lipoproteins in multiple myeloma patients. We also propose novel mechanisms, linking MM development and progression to blood lipoprotein metabolism. We anticipate that proteomic and lipidomic analyses of serum lipoproteins, along with analyses of their functionality, may improve our understanding and shed light on novel mechanistic aspects of MM pathophysiology.